A study on the potential of sand liquefaction Hazard at Chukai Sentral,Terengganu using Plaxis 2D - Siti Fatimah Sadikon,; Nurul Ashikin Eshri,; Juliana Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2024)
An earthquake is classified as a natural disaster of mother nature. Sometimes, it cannot be predicted when it will occur and difficult to estimate the striking force values and the period of incident. The effect of the earthquake may catastrophic if the magnitude is more than 6 Richter. It had been proved by previous event, an earthquake could cause a huge impact towards the soil condition especially when the saturated soil is soft or loose since the propagation of shear wave and compression could induced the soil liquefaction and gave an effect towards excess pore pressure and effective stress of the soil that may affect the stability of infrastructure such as dam, embankment, and bridge. This study was conducted to analyse the horizontal displacement of soil due to earthquake and to evaluate the possibility of liquefaction at Chukai Sentral, Kemaman, Terengganu, Malaysia. The study was conducted using Plaxis-2D software based on Mohr-Coulomb soil model at magnitude of 5.4 Richter. The Mohr-Coulomb model was selected as its failure occurs when the shear stress acting on the soil reaches a critical value and the shear strength is related to the effective stress acting on it. The analysis was concentrated on the mesh deformation and horizontal displacement. The result shows the mesh deformation and horizontal displacement obtained in the boreholes not more than 6 mm. It is considered as a small deformation and will not trigger to the potential of liquefaction to that area. It can be concluded that the earthquake magnitude of 5.4 Richter is unable to disturb the natural resistance of the soil and structure due to their stiff layer proportion.